Progressive multifocal leukoencephalopathy in a lung transplant recipient: Isolation of John Cunningham (JC) virus from bronchoalveolar lavage - Panchabhai, TanmayS; Choudhary, Chirag; Isada, Carlos; Folch, Erik; Mehta, AtulC (Journal of global infectious diseases, 2016)
Progressive multifocal leukoencephalopathy (PML) is a demyelinating disease of the central nervous system caused by polyomavirus John Cunningham (JC) virus. We report the case of a 60-year-old woman who presented 16 months after right single lung transplant with worsening memory, behavioral problems, emotional lability, and progressive left upper extremity weakness. Magnetic resonance imaging revealed white matter changes suggestive of PML. JC virus infection was confirmed with polymerase chain reaction (PCR) from both the bronchoalveolar lavage (BAL) fluid and cerebrospinal fluid. To our knowledge, this is the first report of PCR isolation of JC virus from a BAL specimen. We also review the two additional cases in the literature that describe PML after lung transplantation. JC virus infection should be considered in the differential diagnosis of lung transplant recipients who develop neurological symptoms. BAL may have a role in the etiologic diagnosis of PML after lung transplantation.